Enhancing Tax Compliance and Citizen Trust: The Case for a Single Tax Jurisdiction in the European Union (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study aims to investigate the implications of establishing a Single Tax Jurisdiction (STJ) within the European Union, focusing on its potential to enhance tax compliance, efficiency, and citizen trust. Utilizing advanced AI analysis techniques, the research examines existing tax frameworks across member states, identifying inefficiencies and disparities that hinder effective tax administration. The methodology involves a comprehensive data analysis of tax compliance rates, administrative capacities, and stakeholder perceptions, supplemented by simulations of potential STJ implementation scenarios. Key findings reveal that a unified tax jurisdiction could significantly reduce compliance costs, streamline administrative processes, and improve revenue generation across diverse economic contexts. Furthermore, the study highlights the importance of transparency mechanisms, such as citizen panels and real-time data sharing, in fostering trust and engagement among taxpayers. Overall, the conclusions suggest that the establishment of an STJ presents a viable pathway for addressing the challenges of fragmented tax systems in the EU. By promoting a more equitable and efficient tax environment, the STJ has the potential to enhance fiscal legitimacy and support deeper economic integration within the Union. The findings underscore the necessity for collaborative efforts among member states to realize the benefits of a unified tax framework while ensuring that citizen concerns and expectations are adequately addressed. We submit a four-pronged approach will be necessary to move forward the EU as a Tax Polity: (1) An EU-MS Tax Partnership (2) A EU Common Tax base (3) The EU as a multilevel Tax administration (4) A Single EU Tax Jurisdiction. Finally, the EU doesn’t generate enough income per capita in comparison to GDP ratio that stands at €7,1 trillion in revenues compared to €24 trillion in GDP. This has a negative impact on the EU’s perceived and real abilities to accumulate wealth hence its potential to develop into a powerful polity.